2021
DOI: 10.1039/d0sc06414a
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature methanation of CO2 over an amorphous cobalt-based catalyst

Abstract: It is discovered that an amorphous transition metal catalyst Co–Zr0.1–B–O could effectively accelerate CO2 methanation, at a rate that is comparable to or even higher than that of some noble metal catalysts under similar conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 49 publications
(44 reference statements)
0
21
0
Order By: Relevance
“…The primary product for all catalysts was CH 4 , with ethane and CO as by-products in high and low activity catalysts, respectively (Le et al, 2017). In a recent study, Tu et al (2021) discovered that adding zirconium (Zr) promoter enabled amorphous Co-Zr 0.1 -B-O catalyst to commence CO 2 methanation at temperatures as low as 140 °C. Maximum catalyst activity was achieved at 180 °C (10.7 mmol CO2 g cat −1 h −1 ) with 78.1% CH 4 yield and 97.8% CH 4 selectivity, on par with noble metal catalysts under similar conditions.…”
Section: Cobaltmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary product for all catalysts was CH 4 , with ethane and CO as by-products in high and low activity catalysts, respectively (Le et al, 2017). In a recent study, Tu et al (2021) discovered that adding zirconium (Zr) promoter enabled amorphous Co-Zr 0.1 -B-O catalyst to commence CO 2 methanation at temperatures as low as 140 °C. Maximum catalyst activity was achieved at 180 °C (10.7 mmol CO2 g cat −1 h −1 ) with 78.1% CH 4 yield and 97.8% CH 4 selectivity, on par with noble metal catalysts under similar conditions.…”
Section: Cobaltmentioning
confidence: 99%
“…Maximum catalyst activity was achieved at 180 °C (10.7 mmol CO2 g cat −1 h −1 ) with 78.1% CH 4 yield and 97.8% CH 4 selectivity, on par with noble metal catalysts under similar conditions. The high catalyst performance could be attributed to: (1) prevalent surface defects and inherent active sites in the amorphous structure, and (2) expansion of active surface area and tuning of oxidation state of surface particles by Zr promoter (Tu et al, 2021). Another study by Li et al (2019) examined the effects of organic acidassisted incipient wetness impregnation for Co catalyst preparation.…”
Section: Cobaltmentioning
confidence: 99%
“…18,19 As a result, the reaction is usually carried out at high temperatures (>300 °C), which is thus accompanied by the endothermic RWGSR as a side reaction. 20 Many kinds of catalysts have been developed based on Co, 20,21 Ni, 22−24 Ru, 25,26 Rh, 27,28 and Pd. 29,30 Mechanistic studies indicate that there are two pathways for the methanation of CO 2 , including (a) the conversion of CO 2 to CO by the RWGSR process, followed by hydrogenative methanation of CO and (b) the cascade hydrogenation of CO 2 with the formation of formate as the intermediate.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Consequently, the overall CO 2 -to-CO conversion rate is enhanced because such a reaction is known to proceed via a redox mechanism over iron-based catalysts involving surface reduction as the rate-determining step . It is noted that many studies have also reported that amorphous catalysts have higher activity. A plausible explanation is that amorphous catalysts tend to produce more defects than the well-crystallized structures …”
mentioning
confidence: 99%